2018
DOI: 10.1534/g3.118.200205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Required for Precise Positioning of Apc2 in Dendrites

Abstract: In Drosophila neurons, uniform minus-end-out polarity in dendrites is maintained in part by kinesin-2-mediated steering of growing microtubules at branch points. Apc links the kinesin motor to growing microtubule plus ends and Apc2 recruits Apc to branch points where it functions. Because Apc2 acts to concentrate other steering proteins to branch points, we wished to understand how Apc2 is targeted. From an initial broad candidate RNAi screen, we found Miro (a mitochondrial transport protein), Ank2, Axin, spas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
3
9
0
Order By: Relevance
“…Consistent with a role in localizing γTub, a functional tagged Axin transgene [53]) concentrates at dendrite branch points (Fig 2A and [27]). We previously showed that fz, fz2, and Gαo are necessary for Axin-GFP branch point localization [27]. After finding that other Wnt signaling proteins act upstream of γTub localization, we wished to confirm that they also play a role in Axin targeting.…”
Section: Arr and Fz Act Upstream Of Dsh And Dsh Acts Upstream Of Axisupporting
confidence: 69%
See 4 more Smart Citations
“…Consistent with a role in localizing γTub, a functional tagged Axin transgene [53]) concentrates at dendrite branch points (Fig 2A and [27]). We previously showed that fz, fz2, and Gαo are necessary for Axin-GFP branch point localization [27]. After finding that other Wnt signaling proteins act upstream of γTub localization, we wished to confirm that they also play a role in Axin targeting.…”
Section: Arr and Fz Act Upstream Of Dsh And Dsh Acts Upstream Of Axisupporting
confidence: 69%
“…Cells also expressed either UAS-Rtnl2 RNAi (control 1) (VDRC 33320) (left) or UAS-Axin RNAi (VDRC 7748) (right). (C) A summary of data in earlier figures as well as some previous data [27] is shown. (D) Quantification of EB1-GFP comet direction in the main trunk of the ddaE dendrite in animals expressing hairpin RNAi's.…”
Section: Wnt Signaling Proteins Are Required To Increase Microtubule mentioning
confidence: 94%
See 3 more Smart Citations